2018
DOI: 10.1080/15592324.2018.1430544
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular crosstalk between catalytic activities of receptor kinases

Abstract: Signal modulation is important for the growth and development of plants and this process is mediated by a number of factors including physiological growth regulators and their associated signal transduction pathways. Protein kinases play a central role in signaling, including those involving pathogen response mechanisms. We previously demonstrated an active guanylate cyclase (GC) catalytic center in the brassinosteroid insensitive receptor (AtBRI1) within an active intracellular kinase domain resulting in dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Notably, the AtLRRAC1 1-232 activity is one order of magnitude higher than AtKUP7 that generated 42.5 fmol/μg protein (Al-Younis et al, 2015) but is 1-5 times lower than the typical animal ACs. We also noted that plant nucleotide cyclases (ACs and GCs) have shown consistently lower activities than their animal counterpart, presumably due to a more intricate regulatory role afforded to such AC and GC centers that may enable plant cells to rapidly switch from one cyclic mononucleotide-dependent signaling network to another in localized cellular microenvironments (Muleya et al, 2014;Wong et al, 2015;Irving et al, 2018;Kwezi et al, 2018).…”
Section: In Vitro Ac Activity Of Recombinant Atlrrac1 1-232mentioning
confidence: 91%
“…Notably, the AtLRRAC1 1-232 activity is one order of magnitude higher than AtKUP7 that generated 42.5 fmol/μg protein (Al-Younis et al, 2015) but is 1-5 times lower than the typical animal ACs. We also noted that plant nucleotide cyclases (ACs and GCs) have shown consistently lower activities than their animal counterpart, presumably due to a more intricate regulatory role afforded to such AC and GC centers that may enable plant cells to rapidly switch from one cyclic mononucleotide-dependent signaling network to another in localized cellular microenvironments (Muleya et al, 2014;Wong et al, 2015;Irving et al, 2018;Kwezi et al, 2018).…”
Section: In Vitro Ac Activity Of Recombinant Atlrrac1 1-232mentioning
confidence: 91%
“…The PCR product was then cloned into a pTrcHis2-TOPO expression vector via the TA cloning system (Invitrogen Corp., Carlsbad, CA, USA) to make a pTrcHis2-TOPO:AtCIAP-AC fusion expression construct with a C-terminus His purification tag. Expression, purification and refolding processes of the recombinant AtCIAP 261−379 protein were undertaken as is detailed elsewhere [ 17 , 18 ] and in Appendix A . The relative molecular mass of the AtCIAP 261−379 was estimated using the ProtParam tool on the ExPasy Proteomics Server ( ) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…We also note that since the discovery of the first GC, AtGC1, in 2003 [ 13 ], several GC ([ 3 ], for review see) and AC centres have been identified in AtPPR-AC [ 9 ], AtKUP7 [ 12 ], ZmPSiP [ 8 ] and NbAC [ 10 ]. Importantly, these functional catalytic centres have been shown to play important signalling roles e.g., acting as intramolecular cross-talks between catalytic activities or as molecular switches [ 5 , 17 ] and have varying biological implications [ 6 , 18 , 19 ]. It is now widely agreed that there are two groups of GCs, one the canonical GC domains in often stand-alone molecules and the other, GC centres found usually in multi-domain protein complexes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…GC-kinases have been postulated to serve as a switch between downstream kinase-mediated and cGMP-mediated signaling cascades to elicit desired responses to particular stimuli ( Freihat et al, 2014 ). According to the new mechanism of “moonlighting proteins” cGMP may be acting autonomously at the site where it is produced by regulating the kinase activity of the protein ( Kwezi et al, 2018 ). Comparatively low levels of cGMP synthetized by the GC center in a highly localized region in response to a ligand binding are necessary to inhibit the kinase activity of this type of receptor.…”
Section: Cnmp-dependent Protein Kinases In Plantsmentioning
confidence: 99%
“…Mathematical modeling of cNMP regulation may identify new mechanisms that are involved in the synthesis, action and degradation of cNMP. Firstly, the creation of new bioinformatics tools, such as the recently reported “GCPred” tool for predicting the GC functional center will significantly improve the search for new candidate cNMP-related proteins ( Kwezi et al, 2018 ). Secondly, the development of a fast and non-complicated screening system for potential plant cNMP PDEs would facilitate a quick analysis of selected sequences with predicted PDE activity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%